Improved general circulation models of the Martian atmosphere from the surface to above 80 km - Forget, F; Hourdin, F; Fournier, R; Hourdin, C; Talagrand, O; Collins, M; Lewis, SR; Read, P; Huot, J (1999)
We describe a set of two "new generation" general circulation models of the Martian atmosphere derived from the models we originally developed in the early 1990s. The two new models share the same physical parameterizations but use two complementary numerical methods to solve the atmospheric dynamic equations. The vertical resolution near the surface has been refined, and the vertical domain has been extended to above 80 km. These changes are accompanied by the inclusion of state-of-the-art parameterizations to better simulate the dynamical and physical processes near the surface (boundary layer scheme, subgrid-scale topography parameterization, etc.) and at high altitude (gravity wave drag). In addition, radiative transfer calculations and the representation of polar processes have been significantly improved. We present some examples of zonal-mean fields from simulations using the model at several seasons. One relatively novel aspect, previously introduced by Wilson [1997], is that around northern winter solstice the strong pole to pole diabatic forcing creates a quasi-global, angular-momentum conserving Hadley cell which has no terrestrial equivalent. Within such a cell the Coriolis forces accelerate the winter meridional flow toward the pole and induce a strong warming of the middle polar atmosphere down to 25 km. This winter polar warming had been observed but not properly modeled until recently. In fact, thermal inversions are generally predicted above one, and often both, poles around 60-70 km. However, the Mars middle atmosphere above 40 km is found to be very model-sensitive and thus difficult to simulate accurately in the absence of observations. Copyright 1999 by the American Geophysical Union.